Імітаційно-синергетичне моделювання формування протестної активності - Польовий, Микола Анатолійович; Полевой, Николай Анатольевич; Polevoj, N. (My University, 2012)
Possibilities of imitation-synergetics simulation of protest political activity are considered in the article. Authorial modifi cation of J. Davies model for simulation of dissipative forming of protest activity during an electoral process is offered.
Полевий М. А. Імітаційно-синергетичне моделювання формування протестної активності / М. А. Полевий // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С.164-176.
Keywords: протестна політична активність; моделювання протестної політичної активності; формування протестної активності під час виборчого процесу; модифікація моделі Дж. Девіса; протестная политическая активность; моделирование протестной политической активности; формирование протестной политической активности во время избирательного процесса; модификация модели Дж. Девиса; protest political activity; Modeling protest political activity; the formation of political protest activity during the election process; modification of the model J. Davis